'Northern, not Nordic noir': A Norwegian case study on crime series and strategies for transnational television. Issue 2 (1st June 2021) - Sand, Stine Agnete; Vordal, Thomas
This article discusses transnational television and what strategies public service broadcaster NRK Drama has pursued to make the Norwegian crime series Monster: Brutally Far North travel. Monster was the first Norwegian-language television series bought by a major American cable network, Starz. Using the concept of production values, we argue that NRK has made a series that is able to ride the Nordic noir wave of success while also offering a new northern Norwegian version of the western. These two factors made Monster a good fit for the American market. The series is a result of strategic changes within NRK Drama and a commitment to the private and regional film business. Furthermore, NRK views drama productions as key for reaching audiences and has increased their budgets significantly. The analysis encompasses the industry context, media articles, the 'North' as location, the series itself and interviews with important stakeholders.